PENGARUH MODEL PEMBELAJARAN MULTILITERASI TERHADAP KETERAMPILAN MEMBACA SISWA KELAS IV SDN JAPANAN 2 GUDO - Yunianti, Astri Rizke; Raharja, Hawwin Fitra; Salamah, Evi Rizqi (Prodi Pendidikan Guru Sekolah Dasar, 2024)
Apart from teaching scientific subjects, education in Indonesia in the 21st century also teaches multicultural, multicontextual and multimedia subjects. These elements certainly require a learning model that is appropriate to the subject being studied. Students in elementary schools are guided by using multiliteracy learning strategies to improve their reading skills, especially in Idioms learning. Indonesia. The aim of this study is to find out and characterize how the multiliteracy model influences children's reading skills. The authors of this study used quantitative methods using a one group pretest-posttest design. Data collection techniques use test observations and documentation. Data analysis uses a paired sample test. The subjects in this study were all of the fourth grade students at SDN Japanan 2 Gudo. The significance of the score obtained is 0.00, less than 0.05. These findings show that the multiliteracy model increases the effectiveness and efficiency of Indonesian language teaching, as well as improving the reading comprehension of fourth grade students in elementary schools.